In vitro synergism of colistin in combination with N-acetylcysteine against Acinetobacter baumannii grown in planktonic phase and in biofilms. (29th May 2018) - Pollini, Simona; Boncompagni, Selene; Di Maggio, Tiziana; Di Pilato, Vincenzo; Spanu, Teresa; Fiori, Barbara; Blasi, Francesco; Aliberti, Stefano; Sergio, Francesco; Rossolini, Gian Maria; Pallecchi, Lucia
Abstract: Objectives: To investigate the potential synergism of colistin in combination with N -acetylcysteine against Acinetobacter baumannii strains grown in planktonic phase or as biofilms. Methods: Sixteen strains were investigated, including nine colistin-susceptible (MIC range 0.5–1 mg/L) and seven colistin-resistant (MIC range 16–256 mg/L) strains. Synergism of colistin in combination with N -acetylcysteine was investigated by chequerboard assays. The activity of colistin/ N -acetylcysteine combinations was further evaluated by time–kill assays with planktonic cultures (three colistin-resistant strains and one colistin-susceptible strain) and by in vitro biofilm models (three colistin-resistant and three colistin-susceptible strains). Results: Chequerboard assays revealed a relevant synergism of colistin/ N -acetylcysteine combinations with all colistin-resistant strains, whereas no synergism was observed with colistin-susceptible strains. Time–kill assays showed a concentration-dependent potentiation of colistin activity by N -acetylcysteine against colistin-resistant strains, with eradication of the culture by combinations of N -acetylcysteine at 8000 mg/L plus colistin at 2 or 8 mg/L. A static effect during the first 8 h of incubation was demonstrated with the colistin-susceptible strain exposed to 0.25 × MIC colistin plus 8000 mg/L N -acetylcysteine. A remarkable antibiofilm synergistic activity of 8 mg/L colistin plus 8000 mg/L N -acetylcysteine was demonstrated with all colistin-resistant and colistin-susceptible strains. The effects were greater with colistin-resistant strains (marked reduction of viable biofilm cells was observed at sub-MIC colistin concentrations). Conclusions: N -acetylcysteine, at concentrations achievable by topical administration, was shown to revert the colistin-resistant phenotype in A. baumannii, and to exert a relevant activity against biofilms of colistin-susceptible and colistin-resistant A. baumannii strains.